{Synthesis and biological evaluation of novel 1 '-branched and spironucleoside analogues} - Chatgilialoglu, C; Ferreri, C; Gimisis, T.; Roberti, M; Balzarini, J.; De Clercq, A E (Nucleosides Nucleotides {&} Nucleic Acids, 2004)
Novel anomeric spironucleosides and 1'-cyano-2',3'-didehydro-2',3'-dideoxyuridine, a structural analogue of known anti-HIV agent, were prepared by nucleophilic addition of organolithium reagents to 1'-cyano-2'deoxy- and 1'-cyano-2'-deoxy-2'beta-bromouridine derivatives, respectively. The yield and distribution of products depended on the reaction conditions, whichwere studied in detail. Although none of the compounds exhibited antiviral activit, twocompounds displayed cytostatic activity against both murine leukemia and human T-lymphocyte cells.